2007
DOI: 10.1002/art.22633
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic polyangiitis presenting as a “pulmonary‐muscle” syndrome: Is subclinical alveolar hemorrhage the mechanism of pulmonary fibrosis?

Abstract: Microscopic polyangiitis (MPA) may present with a syndrome that resembles idiopathic pulmonary fibrosis (IPF). We describe an MPA patient with the clinical presentation of a “pulmonary‐muscle” syndrome in which interstitial lung disease antedated the onset of myopathy. Identification of vasculitis on muscle biopsy was instrumental in recognizing clinical, radiographic, and histopathologic features that were more characteristic of MPA than of IPF. Institution of glucocorticoid and cyclophosphamide therapy led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 23 publications
(20 reference statements)
0
40
2
2
Order By: Relevance
“…Previous studies demonstrated that patients with AAV may have subclinical alveolar hemorrhage (9,39), which may cause subsequent pulmonary fibrosis in MPA (40). However, the patients with clinically apparent DAH in our study were less likely to show a reticular pattern.…”
Section: Discussioncontrasting
confidence: 62%
“…Previous studies demonstrated that patients with AAV may have subclinical alveolar hemorrhage (9,39), which may cause subsequent pulmonary fibrosis in MPA (40). However, the patients with clinically apparent DAH in our study were less likely to show a reticular pattern.…”
Section: Discussioncontrasting
confidence: 62%
“…Recurrent occult alveolar haemorrhage has been suggested as a putative mechanism leading to fibrosis, in a manner similar to that described for pulmonary fibrosis in patients with idiopathic haemosiderosis and haemoptysis [6,22]. Subclinical alveolar haemorrhage is frequently detected in patients with ANCA-associated vasculitides and pulmonary disease [23].…”
Section: Discussionmentioning
confidence: 93%
“…Diffuse alveolar haemorrhage secondary to pulmonary capillaritis is the most frequent manifestation of respiratory involvement, expressed clinically as haemoptysis, dyspnoea and anaemia [2,3]. Recently, case reports or small patient series [4][5][6][7][8][9][10][11][12][13][14][15] have also described pulmonary fibrosis in MPA and raised the question that pulmonary fibrosis may also be an important clinical manifestation of the disease. However, the precise prevalence of pulmonary fibrosis and its impact on patient survival remain largely unknown.…”
mentioning
confidence: 99%
“…Classical pulmonary involvement consists of alveolar haemorrhage secondary to pulmonary capillaritis [1,2]. Pulmonary fibrosis is also a potentially severe manifestation of MPA, but mild pulmonary fibrosis is significantly associated with an increased rate of mortality [2][3][4]. Although pulmonary fibrosis in MPA might result from iterative episodes of alveolar haemorrhage, half of patients with pulmonary fibrosis have no history of haemoptysis and pulmonary fibrosis can be the initial manifestation of the disease, sometimes several years prior to the diagnosis of MPA [2,5].…”
mentioning
confidence: 99%